INTEGRATION OF ISLAMIC ECONOMIC VALUES INTO IRE-BASED CHARACTER EDUCATION: A STUDY OF STUDENTS AT PRIVATE UNIVERSITIES IN MATARAM - Baiq Mulianah; Dewi Puspita Ningsih; Ahmad Fauzan; Galih Suryadmaja; Lalu Rohadi Rahman (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This study examines the integration of Islamic economic values into character education within Islamic Religious Education (IRE) among students at private universities in Mataram, Indonesia. It responds to the need to move character education beyond normative religious instruction by connecting Islamic teachings with ethical economic awareness and students’ everyday practices. Using a qualitative case study design, data were collected from lecturers, students, curriculum documents, and classroom learning activities through in-depth interviews, participant observation, and document analysis. The data were analyzed thematically through coding, categorization, and interpretation to identify patterns of value integration. The findings show that honesty, trustworthiness (amanah), justice, responsibility, and economic self-reliance are integrated through contextual, reflective, and transformative learning strategies. These strategies link Islamic economic principles with students’ lived experiences, including consumption ethics, financial responsibility, entrepreneurship, and social concern. The integration is strengthened by lecturers’ moral exemplarity, curriculum design, and an academic environment that supports value internalization. The study concludes that IRE-based character education becomes more effective when Islamic values are embodied as ethical practices rather than transmitted as abstract norms. It contributes to an integrative model of Islamic character education in higher education.